Ground reaction forces during competitive track events: a motion based assessment method - Udofa, A.; Ryan, L.; Clark, K.; Weyand, P. (ISBS Proceedings Archive (Michigan), 2017)
A motion based approach to generating vertical ground reaction forces (VGRF) from the motion of sprint running could be a useful analytical tool. The spring-mass model has been used for this purpose; however, the invariant pattern predicted by the model is not fully consistent with the force-time waveforms of competitive sprint athletes. The recently introduced two-mass model provides an alternative method that might generate better representations of sprinter`s force-time waveforms. Here we used both models to generate kinematic-averaged force-time waveforms from 4 sprint athletes in an IAAF 100-meter race from 360 Hz video data. We found substantial differences in the waveform patterns predicted by the two models. The two-mass model predicted waveform had greater peak forces (4.75 Wb) that occurred earlier in contact (28 ms) vs that of the spring mass model.